2013
DOI: 10.1111/j.1365-2265.2012.04333.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol metabolism after weight loss: associations with 11 β‐HSD type 1 and markers of obesity in women

Abstract: Long-term weight loss in women is not only followed by reduced glucocorticoid production, but also favourably decreases the global and tissue-specific activity of the cortisol-activating enzyme 11 β-HSD type 1, possibly contributing to the health benefits of bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
4
26
0
1
Order By: Relevance
“…Normal human eosinophil had glucocorticoid receptor which was capable of mediating biologic effects at physiologic hormonal concentrations [24]. In obesity, because of a down regulation of 11 β-HSD type 1 in the liver in parallel with an up regulation of the enzyme in adipose tissue [25], as well as because of increased plasma ACTH levels [26], cortisol production had a net increase. As a result, glucocorticoids may enhance eosinophil apoptosis through the intracellular glucocorticoid receptors [27].…”
Section: Discussionmentioning
confidence: 99%
“…Normal human eosinophil had glucocorticoid receptor which was capable of mediating biologic effects at physiologic hormonal concentrations [24]. In obesity, because of a down regulation of 11 β-HSD type 1 in the liver in parallel with an up regulation of the enzyme in adipose tissue [25], as well as because of increased plasma ACTH levels [26], cortisol production had a net increase. As a result, glucocorticoids may enhance eosinophil apoptosis through the intracellular glucocorticoid receptors [27].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying different cortisol excretion pathways and function in different fat depots were not investigated. Studies in bariatric patients showed a decrease of 11β-HSD1 expression and cortisol secretion after weight loss [55], suggesting that regulation of 11β-HSD1 pathway may be dependent on intrinsic factors within adipose tissue. 11β-HSD1 expression is increased by NF-κB, a key mediator of inflammation, and decreased by hypoxia inducible factor-1α (HIF-1α) [56].…”
Section: Cortisol Metabolism In Watmentioning
confidence: 99%
“…Studies on the nutritional regulation of 11β-HSD1 have focused on the effects of lipidogenic diets (Morton et al, 2004;London and Castonguay, 2011;Auvinen et al, 2012;Fernando et al, 2013), dietaryinduced obesity and weight reduction treatment (London and Castonguay, 2009;Simonyte et al, 2010;Rask et al, 2013), as well as of food restriction on 11β-HSD-1 in adipose tissue (Arai et al, 2004). To our knowledge, the effect of calorie restriction on 11β-HSD1 expression in the liver has not been investigated as yet.…”
Section: Abstract the Joint Effects Of Energy Restriction And Age Onmentioning
confidence: 99%